CHLORIDE ION REGULATION IN AN EYESTALK-ABLATED PRAWN PENkEUS INDICUS H. MILNE EDWARDS - Kiron, V; Diwan, A D (Indian Journal of Fisheries, 2011)
The removal of the eyestalks caused a substantial increase in the haemolymph-chloride level in batches of prawns, Penaeus indicus, kept in laboratoryand, when the eyestalk exitract was injected into them, the chloride level decreasedagain and reverted back | tp normal. The findings are deemed as a pointer tothe possible role of eyestalk endocrines in ionic regulation.